2017
DOI: 10.1177/0269094217722336
|View full text |Cite
|
Sign up to set email alerts
|

Narrative of the night-out: Student engagement in the night-time economy of Kingston upon Thames

Abstract: This research programme was part-funded by Kingston Town Centre Management Ltd (Kingstonfirst) and its stakeholders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…Geographers add novel conceptualisations and knowledge to the spatial and temporal patterns of university students' presence in and impacts on cities, such as 'studentification' (Smith 2005;Smith & Holt 2007;Sage, Smith & Hubbard 2012;Smith & Hubbard 2014;Nakazawa 2017) and 'studentscapes' (Russo & Tajter 2007). They also provide numerous insights into the physical, temporal, social and cultural aspects of the leisure consumption of higher education students (Hollands 1995;Chatterton 1999;Smith 2005;Calvo 2017;Fabula et al 2017;Gant & Terry 2017). By contrast, economists measure students' expenditures (e.g.…”
Section: University Students and The Leisure Economy In Contemporary mentioning
confidence: 99%
See 1 more Smart Citation
“…Geographers add novel conceptualisations and knowledge to the spatial and temporal patterns of university students' presence in and impacts on cities, such as 'studentification' (Smith 2005;Smith & Holt 2007;Sage, Smith & Hubbard 2012;Smith & Hubbard 2014;Nakazawa 2017) and 'studentscapes' (Russo & Tajter 2007). They also provide numerous insights into the physical, temporal, social and cultural aspects of the leisure consumption of higher education students (Hollands 1995;Chatterton 1999;Smith 2005;Calvo 2017;Fabula et al 2017;Gant & Terry 2017). By contrast, economists measure students' expenditures (e.g.…”
Section: University Students and The Leisure Economy In Contemporary mentioning
confidence: 99%
“…Put briefly, much of the prior research on students' leisure practices focused mainly on their nights out (e.g. Hollands 1995;Chatterton 1999;Brands, Schwanen & van Aalst 2014;Gant & Terry 2017). Considered in this light, the evidence from Lodz and Turin shows that there are students who do regularly party in music and night clubs, but their number is far smaller than those who prefer other, more 'mundane' types of leisure (such as practising sports or watching films in cinemas).…”
Section: The Role Of Students' Leisure Consumption For Their Host Citiesmentioning
confidence: 99%
“…However, more research about other social and economic roles of students in cities is still merited. For instance, some authors have demonstrated that they are the consumer group that is fuelling the growth of the leisure industry in cities (Malet Calvo, 2018;Chatterton, 2010;Collins, 2010;Gant and Terry, 2017). Others, although not always with a specific urban focus, have implied that they are active participants of job markets, especially in relation to the service industry (Bahrainwala, 2020;Curtis and Lucas, 2001;Munro et al, 2009;Robotham, 2012;Rokita-Poskart, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Levels of alcohol consumption within the mainstream student population is a public health concern in many countries within the Western world, for example the UK ( Gant & Terry, 2017 ; John & Alwyn, 2014 ; Quigg, Hughes, & Bellis, 2013 ), USA ( Ali & Dwyer, 2010 ; Borsari, Murphy, & Barnett, 2007 ), Australia ( Fry, 2011 ; Hepworth et al, 2016 ) and New Zealand ( Hebden, Lyons, Goodwin, & McCreanor, 2015 ; Niland, Lyons, Goodwin, & Hutton, 2013 ). Social norms around drinking within the student population are an important international consideration as to why binge drinking has become commonplace; excessive drinking now has an important role in socialising and reinforcing peer group identity ( Anderson, 2013 ; Gant & Terry, 2017 ; Griffin, Smith, Freeman, & Adams, 2018 ; Hebden et al, 2015 ). Peers often influence drinking practices prior to starting university and young people will often overestimate the amounts of alcohol that their peers are consuming ( Ali & Dwyer, 2010 ) and this continues once young people start university.…”
Section: Introductionmentioning
confidence: 99%